Predicting the risk of cancer after unprovoked venous thromboembolism: external validation of the RIETE score. (24th October 2017) - Bertoletti, L.; Robin, P.; Jara‐Palomares, L.; Tromeur, C.; Pastre, J.; Prevot‐Bitot, N.; Mouneh, T.; Le Gal, G.; Salaun, P.‐Y.; ,
Abstract : Essentials Patients at high‐risk of occult cancer may benefit from extensive screening. We validated the RIETE cancer score in the MVTEP study. One in three patients were classified as high‐risk, 10% of whom had cancer diagnosed. The RIETE score identifies a subgroup at high risk for cancer. Summary: Background: Most recent trials evaluating extensive screening strategies for occult cancer in patients with unprovoked venous thromboembolism have failed, because, among other reasons, of an overall low rate of occult cancer. The RIETE investigators recently proposed a score aimed at identifying a subgroup at higher risk. Methods: We retrospectively computed the RIETE score for all patients included in the MVTEP study, which evaluated the accuracy of [¹⁸F]fluorodeoxyglucose‐positron emission tomography in the screening of occult cancer in patients with unprovoked venous thromboembolism. Performance of the RIETE score was assessed according to the proportion of patients classified in each risk group, and the corresponding rates of cancer diagnosis. Results: Among the 386 patients included in the analysis, 136 patients (35.3%) were classified as high risk by the RIETE score. Cancer was diagnosed in 16 (11.8%) of them, whereas it was diagnosed in nine (3.6%) of the 250 patients with a low RIETE cancer score: odds ratio of 3.6 (95% confidence interval [CI] 1.53–8.32). The area under the receiver operating characteristic curve was 0.63 (95% CI 0.51–0.74). Conclusion: The RIETE score seems to be able to identify a subgroup at high risk for cancer (10%) in our specific dataset of patients with unprovoked venous thromboembolism.